2000
DOI: 10.1071/rd99059
|View full text |Cite
|
Sign up to set email alerts
|

Muscle growth, cell number, type and morphometry in single and twin fetal lambs during mid to late gestation

Abstract: Muscle growth, myofibre number, type and morphometry were studied in large hindlimb muscles of single and twin fetal lambs during mid to late gestation. Placental insufficiency, evident by lower total placentome weight and number per fetus, resulted in reduced fetal weights from 100 to 140 days gestation in twins compared with singletons (at 140 days: 5016 108 g v. 5750 246 g, respectively; P<0.05). However, competition between littermates did not consistently reduce muscle mass (15–22%) until 140 days gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 23 publications
4
23
0
Order By: Relevance
“…5), which is similar to the results of McCoard et al (2001). Four TNNT isoforms have been found in ten different muscle groups in bovine (Muroya et al, 2003c).…”
Section: Discussionsupporting
confidence: 89%
“…5), which is similar to the results of McCoard et al (2001). Four TNNT isoforms have been found in ten different muscle groups in bovine (Muroya et al, 2003c).…”
Section: Discussionsupporting
confidence: 89%
“…Accumulation of myonuclei in foetal ovine skeletal muscle is nutritionally mediated (Greenwood et al, 1999;McCoard et al, 2000), being relating to IGF-1 and -II stimulating both proliferation and differentiation of myoblasts and satellite cells in both a time and concentration-dependent manner Fahey et al, 2005b). Indeed in another species, namely the pig, a reduction in plasma IGF-1 caused by undernutrition compared with adequately fed animals, has been associated with a dramatic alteration in fibre type proportions of m. Longissimus dorsi, m. Soleus and m. Rhomboideus .…”
Section: Lamb Production Performancementioning
confidence: 99%
“…Previously, Greenwood et al (1999 and did not observe differences in myofibre number, but decreased muscle weights, muscular DNA, RNA and protein contents and cell cycle activity at low foetal or birth weight. Similarly McCoard et al (2000) found no differences in myofibre number comparing single and twin lamb foetuses. Moloney and Drennan (2006) studied the effects of birth weight on growth and carcass quality in Charolais cattle and found heavier carcasses that tended to be leaner from high birth weight (54.1 kg) compared with low birth weight (41.4 kg) calves, whereas meat quality characteristics remained unaffected.…”
Section: Regulation Of Myogenesis and Environmental Impactmentioning
confidence: 87%